The effects of using geometry software supported by digital daily life photographs on geometry learning - ÖZDENER DÖNMEZ, NESRİN (ELSEVIER SCIENCE BV, 2010)
Dynamic geometry software has a significant place in geometry instruction, which has been confirmed by many research findings. This study aims to investigate the effects of using geometry software supported by digital photographs that exemplify daily life, upon achievement and permanence of knowledge. The findings of this research demonstrate that using Geometer's Sketchpad (GSP) supported by digital photographs results in improvements in achievement, permanence of knowledge and relating mathematics subjects to daily life. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Geometry instruction; dynamic geomtry software; digital photograph; daily life